Antimony anchored in MoS2 nanosheets with N-doped carbon coating to boost potassium storage performance. (January 2023) - Suo, Guoquan; Zhang, Jiaqi; Li, Ran; Ma, Zerun; Cheng, Yan; Ahmed, Syed Musab
Abstract: Potassium ions batteries (PIBs) have been considered as promising energy storage systems owning to potassium rich natural abundances. However, the difficult reaction kinetics and poor cycling of electrode restrict the further development of PIBs. In this work, antimony anchored in MoS2 nanosheets with N-doped carbon coating (Sb/MoS2 /NCs) are prepared and evaluated as anode for PIBs. In the unique Sb/MoS2 /NCs structure, the volume expansion of Sb particles could be effectively buffered by the around MoS2 structure. The defects in MoS2 nanosheets provide more electrochemical reaction sites for sufficient K + insertion/extraction. Furthermore, the N-doped carbon can further accommodate the volume expansion and improve the electronic conductivity of Sb/MoS2 /NCs composites. Due to the above advantages, the Sb/MoS2 /NCs anode delivers a capacity of 235 mAh/g at 50 mA/g after 78 cycles. This work provides a prospective strategy to design advanced anode materials for PIBs using MoS2 and antimony composites. Highlights: Sb anchored in MoS2 nanosheets with N-doped carbon coating are synthesized via freeze-drying process for potassium storage. The hetero-interface between Sb and MoS2 ensures fast electrons transportation with the help of built-in electric field. The Sb/MoS2 /NCs composite behaves with enhanced potassium storage performance compared with pure MoS2 .